The Principle of Non Discrimination Against the Unilateral Determination of Payment Method Provisions in Non Cash Buying and Selling Transactions - Alizcia Dora Parhusip; Iwan Erar Joesoef (UNIVERSITAS PAKUAN, 2026)
References A. Laws and Regulations Regulation of Members of the Board of Governors Number 3 of 2025 concerning the Third Amendment to Regulation of Members of the Board of Governors Number 21/18/PADG/2019 concerning the Implementation of National Standards Quick Response Code for Payments Bank Indonesia Regulation No. 17/3/PBI/2015 of 2015 concerning the Obligation to Use Rupiah in the Territory of the Unitary State of the Republic of Indonesia Constitution of the Republic of Indonesia in 1945. Law Number 7 of 2011 concerning Currency Law Number 8 of 1999 concerning Consumer Protection B. Books Ali, Zainuddin. Legal Research Methods. Jakarta: Sinar Grafika, 2022. Barkatullah, Abdul Halim. Consumer rights. Nusamedia, 2020. Joesoef, Iwan Erar, Sp N. SH, and M. Kn. Legal Theory: Dogma-Theory-Philosophy. Image Aditya Bakti, 2021. Christian, Celina Tri Siwi. Consumer protection law. Sinar Grafika, 2022. Sihombing, Agustinus. Consumer Protection Law. CV. Azka Pustaka, 2023. Sriekaningsih, Ana. QRIS and the New Era of Payment Transactions 4.0. Andi Publishers, 2020. C. Scientific Journals/Articles Alifia, Nadhifa, Erwin Permana, and Harnovinsah Harnovinsah.